Use of pregnancy counselling services in Australia 2007-2012 - Julia M. Shelley; Shane Kavanagh; Melissa Graham; Catherine Mayes (Elsevier, 2015)
Abstract Objective: To assess the uptake of Medicare Benefit payments for non‐directive pregnancy support counselling which commenced in November 2006. Methods: Counts of services for pregnancy counselling from 1 July 2007 to 30 June 2012, where a Medicare rebate was paid, were used to calculate age‐, state‐ and provider‐specific rates per 100,000 women aged 15-44 years, and rates per 100,000 births for each study year. Results: Rates of Medicare rebates for pregnancy counselling were low, with a mean of 90.6 services per 100,000 women recorded over the study period. GP services were accessed most frequently, while services provided by allied health professionals averaged less than 5% of those for GPs. The overall rate of services fell in all jurisdictions except Victoria/Tasmania, although services provided by allied health professionals remained steady or rose in all jurisdictions over the study period. Conclusions: There has been a low uptake of pregnancy counselling covered by the Medicare Benefits Item numbers introduced in 2006, especially for services provided by allied health professionals. Due to a lack of available data, the impact on abortion rates is unknown. Implications: Provision of Medicare rebates for pregnancy counselling does not appear to be an effective way of assisting women with unintended pregnancies.